An approach towards the fabrication of energy harvesting device using Ca-doped ZnO/ PVDF-TrFE composite film. (28th September 2020) - Sahoo, Rajesh; Mishra, Suvrajyoti; Ramadoss, Ananthakumar; Mohanty, Smita; Mahapatra, Swapna; Nayak, Sanjay Kumar
Abstract: In this research paper, a flexible piezoelectric energy harvesting device based on Ca-doped ZnO (CaZ) nanofiller reinforced poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) composite film has been fabricated and evidenced with enhanced dielectric, ferroelectric and piezoelectric performances. Additionally, a comparative analysis of the crystalline and morphological behavior of the fabricated composite film with pure PVDF-TrFE films has also been reported. A maximum of 1.32 μC/cm 2 saturated polarization and 0.604 μC/cm 2 remnant polarization values are obtained for the composite film with a coercive field of 41 MV/m. The energy harvesting device fabricated from the CaZ/PVDF-TrFE composite film demonstrated an outstanding rectified output voltage of 3 V under continuous human hand tapping and performed well under an oscillating force, resulting in a peak to peak output voltage of 0.289 V at 0.5 N force. The proposed composite film-based device is expected to be a promising material for energy conversion and sensing in the futuristic energy generator applications. Graphical abstract: Image 1 Highlights: Composite film using Ca-doped ZnO nanofillers and PVDF-TrFE polymer matrix is fabricated into an energy harvesting device. Crystalline property and polar electroactive phase improved, because of the presence of CaZ nanofillers. Enhanced dielectric property flourish the ferroelectric performance of the composite film in attaining a higher value of remnant polarization and coercive field. Piezoelectric performance justifies the role of the composite film in the applications of energy harvesting and force sensing.